ANALISIS KETAHANAN KOROSI PIPA A53 PADA LINGUNGAN OIL SLUDGE DENGAN METODE C-RING - Rony Agista Apriansyah; Sumarji Sumarji; Gaguk Jatisukamto (ROTOR, 2017)
Corrosion is the degradation of the material surface due to reaction with the environment. Steel pipe is one of the materials vulnerable to corrosion because the piping system is always in contact with the outside environment. This research have a purpose to know influence of cold working about corrosion resistance pipe A53 on oil sludge salt water and oil sludge pond environment with c-ring method. Oil sludge is sediment of crude oil thats contain water, sediment, and oil thats can be processed again. The cold working process is carried out by providing bending loads of 114 kg, 140 kg, and 160 kg, and one material without bending. Process of corrosion testing uses weight loss method by weighing the material before it is corroded and after corrosion. Result of test showed that there was an increase of hardness on the material with bending load of 114 kg, 140 kg, and 160 kg respectively of 103.33 BHN, 134.00 BHN, and 187.66 BHN, while the material without bending had a hardness of 93.33 BHN. Corrosion rate on material without bending with oil sludge salt water is 2,12 x 10-2 mmpy while in oil sludge pond equal to 1,67 x 10-2 mmpy. Materials with bending loads of 114 kg, 140 kg, and 160 kg have a corrosion rate of 2.35 x 10-2 mmpy, 2.88 x 10- 2 mmpy, and 4.18 x 10-2 mmpy on oil sludge salt water, and 1.19 x10-2 mmpy, 2.15 x 10-2 mmpy, and 3.09 x 10-2 mmpy on oil sludge pond. Oil sludge of salt water is more reactive than oil sludge pond because it contains sea water composed of NaCl compounds which is a corrosive environment .The given bending load results in strain hardening followed by increased energy on the material so that the corrosion rate increases. Cold treatment provided resulted in cracks on the surface of the material so that the corrosion was localized to the crack and formed pitting. Keywords : A53, Oil Sludge, Strain Hardening, Weight Loss